Thermoeconomic analysis method for optimization of insulation thickness for the four different climatic regions of Turkey - Ucar, Aynur (Pergamon-Elsevier Science Ltd, 2010)
Thermal insulation is one of the most effective energy-conservation measures in buildings. For this reason, the energy savings can be obtained by using proper thickness of insulation in buildings. In this study, the optimum thickness of insulation considering condensed vapor in external walls are found by using. exergoeconomic analysis. The four various cities from four climate zones of Turkey, namely, Antalya, Istanbul, Elazig and Erzurum are selected for the analysis. The optimum insulation thickness for Antalya, Istanbul, Elazig and Erzurum are obtained as 0.038, 0.046, 0.057 and 0.0739 m at indoor temperature of 20 degrees C, respectively. The results show that the optimum insulation thickness at the indoor temperature of 18 and 22 degrees C are determined as 0.0663 and 0.0816 m for the city of Erzurum, respectively. The energy saving for the city of Erzurum is found as 77.2% for the indoor temperature of 18 degrees C, 79.0% for the indoor temperature of 20 degrees C and 80.6% for the indoor temperature of 22 degrees C, when the optimum insulation is applied. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Optimum insulation thickness; Energy savings; Thermoeconomic; Climate regions